The Effect of Irrigation and Fertilizer on the Teak Growth in Western Maharashtra - Sonawane, C.J.; Manjare, M.R.; Ghule, S.T.; Kunjir, N.T.; Jadhav, N.A. (Indian Journal of Agroforestry, 2020)
An experiment was conducted to study effect of irrigation, spacing and fertilizers on the teak growth under the Rahuri condition in Western Maharashtra. The growth trial was planted in July, 1991 in light soil following randomized block design with three replications. Performance due to different treatments was assessed for tree height, collar girth, girth at breast height, bole height, crown spread and bole volume of fixed samples on eight years plantation. The results indicated superiority of monthly irrigation treatment and 1.5 X 1.5 m spacing for plant height and 3X3 m spacing for collar girth and bole volume over other treatments. Â